Let's transform each of the given equations to slope-intercept form (which has the form \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept).
-
Transforming \(-2y = 14 - 6x\): \[ -2y = -6x + 14 \] Now, divide by -2: \[ y = 3x - 7 \] So in slope-intercept form: \[ y = 3x - 7 \]
-
Transforming \(0.4x + 0.2y = 0.6\): \[ 0.2y = -0.4x + 0.6 \] Now, divide by 0.2: \[ y = -2x + 3 \] So in slope-intercept form: \[ y = -2x + 3 \]
-
Transforming \(3y = 6x - 18\): \[ y = 2x - 6 \] So in slope-intercept form: \[ y = 2x - 6 \]
-
For the equation \(9 + 272x = -32y\): First, rearrange it: \[ -32y = -272x - 9 \] Now, divide by -32: \[ y = \frac{272}{32}x + \frac{9}{32} \] Simplifying \(\frac{272}{32} = 8.5\), we have: \[ y = 8.5x + \frac{9}{32} \] Therefore, the slope is \(8.5\) and the y-intercept is \(\left(0, \frac{9}{32}\right)\).
In summary:
- The slope is 8.5.
- The y-intercept as an ordered pair is \(\left(0, \frac{9}{32}\right)\).